(untitled) (American Journal of Islam and Society, 2009)
Tariq Ramadan’s latest book, Radical Reform: Islamic Ethics and Liberation, consists of sixteen chapters divided into four major sections: “On Reform,” “ClassicalApproaches of the Fundamentals of Law and Jurisprudence,” “For a New Geography of the Sources of Law and Jurisprudence,” and “Case Studies.” The author commences by criticizing the process of ijtihad as it currently exists. Although it made things progress for centuries, he finds that ijtihad is highly inadequate, has not resolved the crises faced by Muslims, and has not produced the expected renewal. As far as taqlid is concerned, Ramadan argues that imitating past scholars makes Muslims believe that they can avoid today’s challenges by taking refuge in the past. Ijtihad, he believes, has always been behind the times, simply seeking to interpret Islamic law in light of new changes and developments in society. He is critical of literalist, traditionalist, conservative, and culturally based interpretations of Islam. Arab culture, he points out, is not Islam’s sole culture. Thus if Islam is truly a universal religion, it must provide its followers with the means to approach cultural diversity. The author provides an intelligent criticism of Salafism, which confuses eternal principals with historical models and thereby reduces Islam’s universality to the dream of an impossible return to the past and an irresponsible “nostalgia of origins.”As he points out, many Salafi reductionists cannot distinguish between religion and culture and therefore view diversity and sociocultural evolution as religious innovations. Not only is he critical of most traditional approaches to ijtihad, he is critical of virtually every Islamic movement when it comes to their methods of implementing Islamic law ...